Peri‐Interview Communication in the Otolaryngology Residency Match: The Applicant Perspective. (17th February 2020) - Masciello, Maria; Malekzadeh, Sonya
Abstract : Objectives/Hypothesis: To evaluate peri‐interview communication in the otolaryngology Match from the applicant's perspective. Study Design: Cross‐sectional survey study. Methods: A survey link was emailed to 401 otolaryngology residency applicants from the 2019 Match cycle. Survey items queried peri‐interview communication practices and applicants' attitudes toward communication in the postinterview period. Data were collected anonymously. Qualitative analysis was performed for descriptive statistics. Responses from female and male participants were compared using Fisher exact tests. Results: The survey yielded a 44% (56% male, 44% female) response rate and a 100% completion rate. Of applicants, 18% were told they were ranked to match, and 19% were asked how highly they planned to rank a given program. Interview questions regarding marital status and plans for children were asked to 38% and 12%, respectively. The majority (75%) believe peri‐interview communication should be allowed. Most (65%) participants felt obligated to inform top program(s) of their high rank; however, only 45% of applicants found this to be stressful. Peri‐interview communication may have altered the rank list for 10% of applicants. Of applicants, 96% created their final rank list based on where they most wanted to match rather than where they would most likely match. Conclusions: National Resident Matching Program peri‐interview communication violations occur in the otolaryngology Match at similar rates when compared to other specialties. Although peri‐interview communication can cause significant stress, the majority of otolaryngology residency applicants believe peri‐interview communication should be allowed and do not believe it alters applicants' rank lists. Level of Evidence: NA Laryngoscope, 131:28–32, 2021